Acid-Catalyzed Esterification Pretreatment of High Free Fatty Acid Crude Rice Bran Oil for Biodiesel Production - Tin Mar Lar Thein (2020)
This study investigated the acid-catalyzed esterification of two brands of crude rice bran oil (CRBO) with free fatty acids (FFAs) content of about 8 and 10%, respectively. Experimental variables included reaction time, methanol-to-FFA molar ratio and sulfuric acid content with temperature and stirring speed fixed at 60 °C and 600 RPM, respectively. A central composite design was used initially for sequential experimentation and followed by a Box-Behnken design to refine the optimum process conditions. Results showed that final FFA in CRBO could be reduced to less than 1% FFA in a single-step. The methanol-to-FFA molar ratio had the maximum influence on the esterification process and was followed by the reaction time and amount of catalyst. The optimum conditions for FFA conversion in CRBO were: reaction time 90 and 48 min, 62:1 and 70:1 methanol-to-FFA molar ratio, 22.5 and 20% (w/w) sulfuric acid based on FFA for Brand I and II, respectively. Under these pretreatment conditions, initial FFA was reduced to 0.61 and 0.70%, respectively making the CRBO suitable for biodiesel production.